The Influence Of Job Satisfaction And Motivation On Employee Performance At PT. Santy Abadi Mandiri In Bandar Lampung - Shofia, Mira Anita; Trisnowati, Trisnowati (Jurnal Fokus Manajemen, 2025)
This thesis researches the influence of job satisfaction and motivation on employee performance at PT. Santy Abadi Mandiri in Bandar Lampung. The study is motivated by the phenomenon of job satisfaction issues at PT. Santy Abadi Mandiri, where employee turnover is high due to dissatisfaction among employees. They feel that the incentives they receive are not commensurate with the work and risks involved. Low motivation is evident from employee absenteeism, which is attributed to a lack of recognition and limited career development opportunities. Employee performance targets have not been adequately met due to delays in project completion as set by partners.The aim of this study is to determine whether job satisfaction and motivation affect employee performance at PT. Santy Abadi Mandiri. This thesis employs a quantitative method, with job satisfaction (X1) and motivation (X2) as the independent variables, and employee performance (Y) as the dependent variable. Data collection methods include both primary and secondary sources, utilizing literature review and field research techniques such as observation and questionnaires.The results indicate that job satisfaction and motivation both individually and collectively influence employee performance at PT. Santy Abadi Mandiri. Based on the data analysis, the findings are as follows: (1) Job satisfaction (X1) has an influence on employee performance (Y) with an effect size of 79,6%, (2) Motivation (X2) influences employee performance (Y) with an effect size of 76.3%, (3) Simultaneously, job satisfaction (X1) and motivation (X2) significantly affect employee performance (Y) at PT. Santy Abadi Mandiri, with a combined effect size of 84.5%